Finding the words : working through profound loss with hope and purpose - Campbell, Colin (TarcherPerigee, Penguin Random House LLC, 2023)
"A powerful account of one father's journey through unimaginable grief, offering readers a new vision for how to more actively and fully mourn profound loss. When Colin Campbell's two teenage children were killed by a drunk driver, he was thrown headlong into a grief so deep he felt he might lose his mind. As he began to process his grief, he realized that much of the common wisdom about coping with loss was unhelpful-that it is a private and mysterious process and that the pain is so great that there "are no words." Campbell draws on what he learned from his own journey to offer readers an alternate path for processing their pain that is active and vocal, and truly honors the loved ones they have lost. In Finding the Words, Campbell offers practical advice on how to survive in the aftermath of loss. By actively reaching out to their community, performing mourning rituals, and finding ways to express their grief, readers will learn how to live more fully while still holding their loved ones close. Campbell shines a light on a path forward through the darkness of grief"--